Music in the Head: the Figure of Ludwig van Beethoven as an Acoustic System in Gert Jonke’s “Gentle Rage or the Ear Engineer” - Macenka, Svitlana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. Intermedial studies are an important part of modern humanities requiring literary and music studies to reprofile and set new objectives. Literary studies occupy a principal place in developing theoretical frameworks and categories of intermediality, which, as relevant papers show, are widely used by music studies. Interdisciplinary studies are particularly promising in this respect as they not only promote a more profound look into problematic musical and literary complexes but also contribute to the self-establishment of both disciplines under new media conditions. Artistic literature serves as material for discovering musical and literary connections while relying on music studies achievements. The creativity of the Austrian writer Gert Jonke (1946–2009), in particular, offers narrative strategies and inter-artistic concepts through which the writer ensures the auditory dimension of a work of literature. Research novelty lies in the specification of music and literary connections as a textual performance focusing on the embodiment of music. Research objective is to identify the main trends in contemporary musical and literary intermedial studies and, within this framework, conduct an analysis of the theatre sonata Gentle Rage or the Ear Engineer (“Sanftwut oder Der Orenmaschinist”, 1990) by Gert Jonke, stressing upon the concept of the body as an intermedium. Research methodology consists of a description of the underlying principles of mediality applied to the analysis of Gert Jonke’s drama. Results and conclusions. During the 2020 Ludwig van Beethoven anniversary year, Gert Jonke’s theatre sonata Gentle Rage or the Ear Engineer became a particularly important element of remembering-understanding the artist’s creativity. The works of the Austrian writer are notable for their particular sonority. One of the central motives is that of a head which is associated with the stage where thoughts and sounds unfold practically at the same time. The presence of sounds belongs to the sphere of contrived — it exists in the head (consequently, on stage). From an intermedial perspective, the theatre sonata Gentle Rage or the Ear Engineer (according to Beethoven’s intentions of ideal performance) emerges as a concert in which the sounds are transmitted with the help of digital piano at the moments when the monologs of the protagonist change dialogues. The sounds of sonata rendered by the electronic instruments translate the imagined music in Beethoven’s head to acoustic material, while the dramatic text is simultaneously interpreting the play with its own means. The abstract sonata conceived in mind transforms into an actual acoustic image during its staging, embodied in and through the figure of Beethoven. It is apparent that Gert Jonke considers the auditory experience of recipients and appeals to it using specific moods, harmonies, dissonances, and tempo markings. The central concept of the body as an intermedium relies on musicological musings about the effect of deafness on Beethoven’s late creativity. It is closely connected to certain aspects of interpretation of his late works (absolute music, the opposition of light and darkness).